Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1038/s41537-020-00122-3
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of antipsychotic drugs in schizophrenia: a 10-year retrospective study in a Korean tertiary hospital

Abstract: Extensive research has been carried out on the comparative effectiveness of antipsychotic medications. Most studies, however, have been performed in Western countries. The purpose of this study was to compare the effectiveness, indicated by time to any-cause discontinuation, of antipsychotic drugs in a large number of patients with schizophrenia in South Korea. We identified 1458 patients with schizophrenia or schizophreniform disorder who were treated with antipsychotic medications using a clinical data wareh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 46 publications
0
6
0
1
Order By: Relevance
“…Unlike the influence of gender, ethnicity does not appear to have any impact on treatment response obtained with clozapine[ 115 , 130 ]. On the other hand, there are ethnic differences in pharmacokinetic profiles of clozapine[ 122 ].…”
Section: Preventing Resistance To Clozapine Treatmentmentioning
confidence: 99%
“…Unlike the influence of gender, ethnicity does not appear to have any impact on treatment response obtained with clozapine[ 115 , 130 ]. On the other hand, there are ethnic differences in pharmacokinetic profiles of clozapine[ 122 ].…”
Section: Preventing Resistance To Clozapine Treatmentmentioning
confidence: 99%
“…In addition, a study conducted on ADRs in the psychiatric department of a tertiary care hospital in India reported that olanzapine, risperidone, and haloperidol were most commonly associated with adverse effects (Patel et al, 2015). This discrepancy could be attributed to differences in local prescription patterns and traditions across countries rather than differences in the incidence of ADRs of antipsychotic drugs (Dong et al, 2019; Oh et al, 2020). In Korea, for example, quetiapine has been widely used as it is preferred over other antipsychotics for alleviating sleep problems, as an adjuvant therapy for depression (Kim et al, 2019), and a treatment for delirium in intensive care units (Jung and Lee, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…However, there is little information regarding the characteristics of antipsychotic adverse effects among the Asian population. Because of the differences in the genetic and non-genetic mechanisms that influence pharmacokinetics and epidemiology, ethnicity causes significant differences in drug response and side effects (Chaudhry et al, 2008; Chong et al, 2003; Oh et al, 2020). Thus, a large-scale investigation within the Asian population is warranted.…”
Section: Introductionmentioning
confidence: 99%
“…Second, patients might discontinue or change the antipsychotic treatment regimen because of worsening of symptoms or the onset of other mental health disorders, not because they showed a poor response to their first-line antipsychotic agent. To overcome this limitation, several events indicating the worsening of psychiatric symptoms were included to identify poor treatment results 12 28. Third, it was impossible to include all predictors that might improve the accuracy of the prediction model, such as the type of schizophrenia, disease severity and residential area, due to the lack of data.…”
Section: Discussionmentioning
confidence: 99%